A study of consumer benefit from district heating service in Korea. (June 2019) - Park, Changwon; Jeong, Yoojin; Yoo, Seung Jick
Abstract: Integrated energy supply (IES) produces both heat and electricity simultaneously, improving energy efficiency and reducing air pollutants. As of the end of 2016 in Korea, 16.1% of households received district heating service as the government pushed to expand the integrated energy supply. Since large-scale facilities are installed according to local demand for heat, IES—compared to individual heating systems—can increase the consumer benefit by reducing the annual cost of heating through lower facility costs. This study estimates the consumer benefits of district heating service from IES. We apply the compensated variation (CV) based on the Hicksian welfare concept and evaluate new consumers as well as existing consumers who switch from individual heating to district heating. The estimated CV shows that the new consumer benefit is 1.75 times higher in terms of heating cost if they use district heating from IES; moreover, they benefit 50% more than the Marshallian consumer surplus. Consumers who switch to district heating gain a 24% benefit (economic value/heat price equals 1.24). Electricity produced from IES is an indispensable energy source for industrial production, household appliances, cooking, and lighting and the estimated CV shows that a consumer who uses one unit of electricity enjoys 1.38 times additional benefit. Highlights: 16.1% of households in Korea received district heating service in 2016. District heating provides heating service at lower cost. New consumer's benefit is 1.75 times higher from use of district heating from IES. Consumers switching from individual heating to district heating gain a 24% benefit. District heating, an effective climate change measure, increases consumer welfare.